Disaster preparedness for tourist village organizers in disaster prone area of Merapi Yogyakarta - Wijaya, Oktomi (Periodicals of Occupational Safety and Health, 2023)
Background: A number of tourist villages in Sleman Regency are located in Disaster Prone Area (DPA). To minimize the risks of disasters, preparedness efforts are required. Some of the components of preparedness are: knowledge of disaster risks, polices and guidelines in relation to the preparedness to anticipate the occurrence of natural disaster, emergency plan for natural disasters, disaster alert system, and resources mobilization. Tourist Villages of Pentingsari, Nganggring, and Tunggularum are located in Merapi Disaster Prone Area (DPA). These three tourist villages were selected due to their high vulnerability and risk potential of Merapi eruption due to their locations in DPA III and DPA II. Methods: This is a qualitative study with case study design. The subjects of the study were tourist village organizers who had knowledge and understanding of tourist villages with the criteria of their positions in the tourist village organization. The sample taking technique applied to the subjects was the purposive sampling technique. Results: The level disaster preparedness in terms of knowledge parameter among some tourist village organizers was limited since only few things were understood. In terms of policy and guidelines parameter, these components were not available for the tourist village organizers. With regard to the parameter of emergency plan for the organizers, this component was limited since there were some lack of preparation in a number of components. In relation to the parameter of disaster alert system for the tourist village organizers, this aspect was found to be good. With regard to the parameter of resource mobilization for the tourist village organizers, it was found that this aspect was unavailable since there were not enough decent facilities. Conclusions: the level of disaster preparedness in the disaster prone area of Merapi Yogyakarta was still limited in dealing with the threats of Mount Merapi eruption disaster.